Seller s ’ intention to adopt mobile payment in Klang valley - Chew, Zheng Hui; Tiang, Ming Jie (2019)
The development of technology has changed the way of people performing task. Nowadays, people rely heavily on technology to complete works as technology help to enhance and increase efficiency. Mobile payment has become popular in both businesses and consumers’ context as it contributes many benefits to them. The global mobile payment trend is increasing dramatically as well as in Malaysia. In Malaysia, there are many consumers’ subscriptions however low mobile payment usage compares to other countries in Asia. This is because Malaysian merchants’ adoption rate is relatively low. This objective of this research is to investigate, understand and identify the factors that affect sellers’ intention to adopt mobile payment aiming to understand the reason of low adoption rate among the businesses. The data was collected by using survey questionnaire for this study. These questionnaires were distributed to microbusiness owner that consumers are spent to majorly in retails, hawker stalls, street sellers and restaurants. The researchers used Software Package for Social Sciences (SPSS) to analyse the data collected and shows in tables and diagrams. Base on the results then future discuss the impact and relationship of each factors to the sellers’ intention. Elf This research found out perceived cost, performance expectancy, effort expectancy, s efficacy and perceived security have positively and significantly impact on sellers’ intention to adopt mobile payment. The results contribute for the managerial implication and policy maker to consider when these parties want to increase find ways to the merchants’ adoption rate to boost up the usage of mobile payment in Malaysia. XII